Cooperative Control of Crb2 by ATM Family and Cdc2 Kinases Is Essential for the DNA Damage Checkpoint in Fission Yeast - Nakamura, Toru M. (American Society for Microbiology, 2005)
The cellular responses to double-stranded breaks (DSBs) typically involve the extensive accumulation of checkpoint proteins in chromatin surrounding the damaged DNA. One well-characterized example involves the checkpoint protein Crb2 in the fission yeast Schizosaccharomyces pombe. The accumulation of Crb2 at DSBs requires the C-terminal phosphorylation of histone H2A (known as γ-H2A) by ATM family kinases in chromatin surrounding the break. It also requires the constitutive methylation of histone H4 on lysine-20 (K20). Interestingly, neither type of histone modification is essential for the Crb2-dependent checkpoint response. However, H4-K20 methylation is essential in a crb2-T215A strain that lacks a cyclin-dependent kinase phosphorylation site in Crb2. Here we explain this genetic interaction by describing a previously overlooked effect of the crb2-T215A mutation. We show that crb2-T215A cells are able to initiate but not sustain a checkpoint response. We also report that γ-H2A is essential for the DNA damage checkpoint in crb2-T215A cells. Importantly, we show that inactivation of Cdc2 in γ-H2A-defective cells impairs Crb2-dependent signaling to the checkpoint kinase Chk1. These findings demonstrate that full Crb2 activity requires phosphorylation of threonine-215 by Cdc2. This regulation of Crb2 is independent of the histone modifications that are required for the hyperaccumulation of Crb2 at DSBs.